Bathed in blood : hunting and mastery in the Old South - Proctor, Nicolas W., 1969- (University Press of Virginia, 2002)
"A widely recognized symbol, both at the time and in legend, of the antebellum slaveholding class's aristocratic pretensions, the hunt is obviously deserving of study. In Bathed in Blood, however, Nicolas Proctor makes an excellent case for the cultural and social significance of hunting for all classes and races of antebellum Southern men. He effectively demonstrates that the pursuit of game lay at the confluence of almost all of the key signifiers of masculinity in both white and black culture. Proctor's is the most detailed account and sustained analysis we have of hunting in the Old South. It involves a sophisticated (but, mercifully, mostly jargon-free) cultural analysis of a rich body of literature surrounding the hunt--sporting journal articles, travel accounts, private diaries and correspondence, WPA slave narratives, etc. But this is also a social, and especially in the first chapter an environmental, history of this subject. Proctor lays out the mechanics as well as the meaning of the hunt. In his pursuit of the forms, he never loses sight of the more utilitarian benefits of the hunt--meat and hides. While elite hunters who stressed the ideal rules of sport disdained 'pothunters' (those who hunted for subsistence), the tangible fruits of the hunt were far from irrelevant in their display of mastery. Throughout his account, Proctor carefully distinguishes between the ideal and the real, and pays them both due attention."--A review on H-Net.